Influence of body composition and physical fitness on arterial stiffness after marathon running - Deiseroth, Arne; Nussbaumer, Monique; Drexel, Verena; Hertel, Gernot; Schmidt-Trucksass, Arno; Vlachopoulos, Charalambos; Halle, Martin; Hanssen, Henner (Scandinavian journal of medicine & science in sports, 2018)
Background and aims: Participation in exhaustive endurance sports competitions continues to be popular. Questions about the cardiovascular side effects of prolonged excessive exercise persist. Our study aimed to elucidate the acute effects of marathon running on arterial stiffness (AST) and to detect the role of body composition, fitness status, and inflammation. Methods: Body composition was investigated in lean and obese recreational runners taking part in a marathon race. Fitness levels were determined in advance by a symptom-limited treadmill test to obtain the individual anaerobic threshold. Carotid to femoral pulse wave velocity (PWV), systolic and diastolic blood pressures (BP), and inflammatory markers (TNF-ɑ, IL-6, hsCRP) were measured before 2 hours and 24 hours after a marathon race. Results: A total of 47 male runners with a wide range of body mass index (BMI) and fitness levels took part in the study. Baseline PWV was independent of body composition. Marathon running induced an acute PWV drop from 8.5 m/s to 7.9 m/s within the first two hours after the race (P < 0.05). Body composition and not physical fitness predicted the PWV differences postmarathon (P > 0.05). Changes in BP, heart rate, or inflammatory markers were not associated with PWV postmarathon. Conclusions: Though not evident at baseline, marathon running was associated with a reduced attenuation of central arterial stiffness in overweight and obese runners. The reduced responsiveness and attenuation of PWV with higher BMI, independent of hemodynamic changes and systemic inflammation, may represent masked vascular dysfunction in overweight and obese runners.
CRIS-Team Scopus Importer:2023-03-08
Keywords: arterial stiffness; fitness; inflammation; marathon running; obesity; pulse wave velocity